1992
DOI: 10.1128/cmr.5.1.49-73.1992
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and molecular biology of progressive multifocal leukoencephalopathy, the JC virus-induced demyelinating disease of the human brain.

Abstract: ease are graphically presented in Fig. 1: (A) JC virions as they assemble in the nucleus of an infected cell in the brain; (B) glial cells, cultured from human brain, which are the targets of virus infection; (C) histopathological plaque lesion of white matter, stained for myelin, that results from that infection; (D) hematoxylin and eosin stain of cells in the lesion identified as macrophages (m) and astrocytes (a); and (E) plaques of demyelinated white matter which represent the neurological impairments char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 153 publications
(252 reference statements)
1
104
0
4
Order By: Relevance
“…The presence of JCV DNA in kidneys, lymph nodes, spleen, bone marrow, and liver (8) suggests a widespread hematogenous distribution of the virus in PML patients. The multifocal and perivascular distribution of white matter lesions further supports the putative role of blood cells in the spread of JCV into the central nervous system (12).…”
Section: Discussionmentioning
confidence: 60%
“…The presence of JCV DNA in kidneys, lymph nodes, spleen, bone marrow, and liver (8) suggests a widespread hematogenous distribution of the virus in PML patients. The multifocal and perivascular distribution of white matter lesions further supports the putative role of blood cells in the spread of JCV into the central nervous system (12).…”
Section: Discussionmentioning
confidence: 60%
“…There is indirect evidence from clinical studies that the GAG pathway may be medically relevant for polyomavirus infections. A clinical study involving four patients suggested, speculatively, that systemic heparin treatment might be useful for halting the progression of PML (Major et al, 1992). GAGs have also been investigated as possible treatments for BKV-induced hemorrhagic cystitis following bone marrow transplant (Arthur et al, 1986;Reploeg et al, 2001) and for a potentially BKV/JCV-associated chronic bladder syndrome known as interstitial cystitis (Van der Aa et al, 2014;Winter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that JCV can enter susceptible cells by binding to 5‐hydroxytryptamine (5‐HT) 2A receptors . In addition, a more controversial theory is that JCV re‐activation occurs at sites outside the CNS when host immunity is impaired, and the virus is able to cross the blood‐brain barrier within B lymphocytes . Once it enters the brain, JCV can infect both oligodendrocytes and astrocytes …”
Section: Discussionmentioning
confidence: 99%
“…Finally, PCR screening has been found to have a variable false negative rate . Instead, brain biopsy is currently considered the most accurate tool for diagnosis, and demonstration of JCV DNA in the biopsy sample, or positive histological evidence of JCV antigens in the CNS, is required for a definitive diagnosis of PML. This method has a sensitivity of up to 96%, and a specificity of 100%, and is useful in those who have tested negative for JCV DNA in the CSF using PCR .…”
Section: Discussionmentioning
confidence: 99%